Time is when - Gleick, Beth Youman; Jocelyn, Marthe (Plattsburgh, N.Y. : Tundra Books of Northern New York, 2008)
An illustrated explanation of the passage of time for children, featuring examples of different measurements of time, from one second to one year.
"Originally published in the United States by Rand McNally & Company, 1960"--T.p. verso.
Resource Links.
2.1
K-3
Keywords: Time -- Juvenile literature; Time; Time